Issues of Creating a Multi-Purpose Land Database on the Example of Vobkent District of Bukhara Region - Yu., Mahsudov B. (International Journal on Orange Technologies, 2022)
Today, information on land resources is a key source in ensuring the sustainability of agricultural land relations. The collection of information on land resources by various ministries and agencies, the lack of coordination of the land database shows that the socio-economic management of the regions is not enough to make the right decisions.